Evet, ich will! Hochzeit auf deutsch-türkisch - Ruzicková-Steiner, Gudrun 1942-; Schafmeister, Heinrich 1957-; Westphal, Ingeborg 1951-2012 (Polar Film, 2015)
Romantic comedy about four unusual couples and their struggle for love against multicultural boundaries, where a bridal shop clearance sale is the commonality that connects the couples in pre-wedding turmoil. In their day nearly sixty years ago, the Turkish shop owners had it easy; marriages were arranged by parents. But now, living in Germany, parents are up against passion and cross-cultural complications. Dirk is a charming German, son of well-heeled counter-culture parents who do not find it necessary to marry anyone, including beautiful Ozlem from Turkey. Popular Kurdish radio DJ Coskum should not be so in love with a modern Turkish Alawi girl. Emrah's parents expect him to marry a nice Turkish girl--he loves handsome Tim. Salih has a green card issue and hopelessly seeks a pretty woman to marry just like the woman he loves back home in his native village
Untertitel: deutsch, türkisch, englisch ; Aspect ratio: 16:9
DVD release of 2008 motion picture
Keywords: Interpersonal relations / Drama; Love / Drama; Marriage / Drama; Interpersonal relations; Love; Marriage; Drama; Feature films; Romantic comedy films; Film; DVD-Video